Targeting PKM2 in cancer therapeutics: mechanistic advances and translational opportunities - Liu, Lin; Wang, Junyi; Liang, Libo; Chen, Chunhua; Xie, Meng; Tang, Wencheng (Frontiers in Immunology, 2025)
M2-type pyruvate kinase (PKM2) serves as the key rate-limiting enzyme in aerobic glycolysis within tumor cells, where its aberrantly high expression in numerous human malignancies facilitates tumor progression by enhancing glycolytic flux through diverse signaling pathways. Beyond its metabolic function, extensive studies have established PKM2 as a critical non-metabolic signaling regulator implicated in multiple oncogenic processes, including tumor proliferation, invasion, migration, immune evasion, and resistance to chemotherapy. The elucidation of PKM2-mediated oncogenic pathways has spurred the development of targeted therapeutic strategies, positioning PKM2 as a promising target in cancer therapy. However, comprehensive reviews addressing the relationship between PKM2 and tumorigenesis remain limited. This review systematically examines the biological functions of PKM2, the signaling mechanisms through which it exerts its effects in malignant tumors, and the latest advances in the development of PKM2-targeted therapeutics, offering insights into potential directions for future drug discovery.